Caspases-3 and -7 are activated in goniothalamin-induced apoptosis in human Jurkat T-cells - Inayat-Hussain, Salmaan H.; Osman, Annuar B.; Din, Laily B.; Ali, Abdul M. (Federation of European Biochemical Societies, 1999)
Goniothalamin, a plant styrylpyrone derivative isolated from Goniothalamus andersonii, induced apoptosis in Jurkat T-cells as assessed by the externalisation of phosphatidylserine. Immunoblotting showed processing of caspases-3 and -7 with the appearance of their catalytically active large subunits of 17 and 19 kDa, respectively. Activation of these caspases was further evidenced by detection of poly(ADP-ribose) polymerase cleavage (PARP). Pre-treatment with the caspase inhibitor benzyloxycarbonyl-Val-Ala-Asp fluoromethyl ketone (Z-VAD.FMK) blocked apoptosis and the resultant cleavage of these caspases and PARP. Our results demonstrate that activation of at least two effector caspases is a key feature of goniothalamin-induced apoptosis in Jurkat T-cells.